AB1180 The intensive exercise programme for non-radiographic axial spondyloarthritis and for ankylosing spondylitis may improved quality of life and disease activity. (15th June 2017) - Husakova, M; Pavelka, K; Spiritovic, M; Levitova, A
Abstract : Background: The therapy for axial spondyloarthritis (axSpA) is complex. Although anti-inflammatory medication is necessary for axSpA treament, the exercise therapy is required to maintain mobility. The limited data are available to evaluate the effect of exercise therapy on quality of life in axSpA, particularly in patients with the non-radiographic form of the disease (nr-axSpA). Objectives: To investigated the quality of life in axSpA subgroups, nr-axSpA and Ankylosing spondylitis (AS) in response to intensive rehabilitation programme Methods: 46 patients with axSpA characterised according to criteria of Assessment of SpondyloArthritis international Society (ASAS) as nr-axSpA (n=23) and AS (n=23) with stable disease and treatment underwent 24 weeks long intervention. The intervention consisted in twice a week outpatient group physiotherapy as exercise units of 60 minutes and a daily home-based exercise programme. All outcomes, disease activity (Bath AS Disease Activity Index, BASDAI and AS Disease Activity Index, ASDAS-CRP) and quality of life (AS quality of life, ASQoL and European quality of life, EurQoL) as well as patients self-reported outcomes such as "patients global assessment" and "pain assessment" were measured at baseline and at the end of exercise program. Results: Altogether, 41 axSpA patients (AS, n=22 and nr-axSpA, n=19) finished complete six months programme. The disease activity was improved in all axSpA patients (ASDAS-CRP 2.08±0.12 to 1.83±0.11, p<0.01), particularly in nr-axSpA subgroup, ASDAS-CRP (1.98±0.19 to 1.71±0.15, p<0.05). There were no differences in the changes in ASDAS-CRP and BASDAI over the exercise training between groups (data not shown). After exercise therapy, positive changes of "Patients global assessment", were evaluated by patients of both subgroups, nr-ax-SpA (33.42±5.13 to 23.68±4.11, p<0.01) and AS (35.22±3.94 to 25.2±2.92, p<0.01). The "assessment of pain during the last 7 days", however, was improved only by patients in the nr-axSpA subgroup (34.74±5.88 vs. 21.05±4.71, p<0.05). The quality of life, ASQoL was not changed after rehabilitation programme. The EurQoL was changed in all axSpA (0.74±0.21 to 0.77±0.18 p<0.05), but significantly was improved only in nr-axSpA subgroup (0.72±0.23 to 0.78±0.18, p<0.01), not AS. Similarly, the improvement of the assessment of "hodiernal health status" was found after an intervention only in the nr-axSpA subgroup (65.81±21.80 to 78.00±13.77, p<0.01). Conclusions: Our study demonstrated beneficial effect of intensive exercise programme on disease activity and patients self-reported outcomes in nr-axSpA and AS patients. The patients suffering from nr-axSpA can profit at least similarly from the rehabilitation care as those with radiographic form. The exercise programme should be recommended for both subtypes of axSpA. References: Millner JR, et al. Exercise for ankylosing spondylitis: an evidence-based consensus statement. Semin Arthritis Rheum. 2016;45:411–27. doi: 10.1016/j.semarthrit.2015.08.003. Acknowledgements: This study has been supported by the Project for Conceptual development for institution of Ministry of Health Czech Republic - Institute of Rheumatology (number 023728), by SVV for FTVS UK (number 2016–260346), GAUK (number 214615) and PRVOUK (number P38). Disclosure of Interest: None declared